SISTEM INFORMASI INVENTORI DAN PENJUALAN BERBASIS WEB DI TOKO BANGUNAN ENGGAL JAYA KLATEN - , AKBAR ROSYIDHANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Enggal Jaya material building store engaged in the sales of building materials, which in the process of its item data management and transactionâs still using paper based system. Unfortunately, this system needs a long time to manage data and transaction, also has less of accuracity. To increase the quality of its service, Enggal Jaya material building store needs system which more effective, and more accurate. Include in the process of item data management and transaction. Web-based Inventory Information System adn Point of Sales is useful for managing the item data and transaction, so that this research made a data processor which is more effective, efficient, and accurate. This system using PHP programming language with CodeIgniter and MySQL database. This system is delevoped with interactive design to help the user in the process of data processing. This data processing can be used by users easily due to it has feature search and reporting.